Effect of Low Temperatures on Protein Systems - Nardid, Oleg A. (Problems of Cryobiology and Cryomedicine, 2014)
The review concerns the main issues of preserving the structure and function of proteins either isolated or as a part of biological tissues during hypothermic and cryogenic storage. The role of biomacromolecules’ dehydration, as a consequence of water freeze-out in proteins cryodamage during freeze-thawing is discussed, as well as peculiarities of protein low-temperature denaturation, associated with entropic nature of hydrophobic interactions. Low temperature injuries in biomacromolecules, their reversibility with considering the role of water in structure instability of cooled or frozen biopolymers are described. Potential ways to protect biomacromolecules during freezing are considered. Probl Cryobiol Cryomed 2014; 24(2):83-101.